IN VITRO ANTIMICROBIAL ACTIVITY OF ROOT EXTRACT OF CLITORIA TERNATEA - Rao, Amita Shobha; Kl, Shobha; Md’almeida, Prathibha; Rai, Kiranmai S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Infections caused by Gram-negative bacteria are important causes of morbidity and mortality. Extracts of plants and herbs such as Clitorea ternatea are used as diuretic. This work attempts to find out antimicrobial activity of aqueous and alcoholic extract of C. ternatea roots against Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 25922), clinical strains of Klebsiella pneumoniae, and Candida albicans. Methods: The agar well-diffusion method was done using Mueller Hinton agar and Sabouraud's dextrose agar. The microorganism grown in peptone water was inoculated into culture medium. 4 mm diameter well punched into the agar was filled with 20 μl of aqueous and alcoholic root extracts C. ternatea extracts in various concentrations (100-25 μg/ml). The plates were incubated and antimicrobial activity was evaluated. Results: Aqueous root extract of C. ternatea with the concentration of 100 μg/ml showed zone of inhibition against E. coli (ATCC 25922) 18 mm, P. aeruginosa (ATCC 27853) 14 mm, multidrug resistant strain of K. pneumoniae 15 mm. Alcoholic extract of C. ternatea with the concentration of 100 μg/ml showed zone of inhibition of 35 mm against E. coli (ATCC 25922), P. aeruginosa (ATCC 27853) 22 mm, and multidrug resistant strain of K. pneumoniae 28 mm. C. albicanswas resistant to both extract of C. ternatea root. Conclusions: Alcoholic extract of C. ternatea is a better antibacterial agent against multidrug resistant Klebsiella species and other Gram-negative pathogens. Further, studies are required to identify active substances from the alcoholic extracts of C. ternatea for treating infections.